1981
DOI: 10.1002/jez.1402150203
|View full text |Cite
|
Sign up to set email alerts
|

Preamputation and postamputation histology of the neonatal opossum hindlimb: Implications for regeneration experiments

Abstract: Mammalian limbs generally do not regenerate, regardless of added hormonal or nervous stimulation, whether amputation occurs during fetal life or post-partum. The one exception, the newborn opossum, has been reported to regenerate the incompletely developed hindlimb (Mizell, '68). In an attempt to repeat and extend these earlier findings, we have examined the histology of the neonatal opossum hindlimb. After amputation on day 4 post-partum, we correlated the histology of the amputated segment with the histology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Following the lead of Marcus Singer's studies on the neurotrophic influence in amphibian limb regeneration (Singer, 1952), Mizell reported on induced regeneration of amputated newborn opossum hind limbs by implantation of neural tissues (Mizell, 1968). However, in an effort to replicate these studies, Fleming and Tassava reported that anatomical variability in the timing of skeletal outgrowth of the opossum hindlimb, and not neural tissue grafts, could account for the partial regenerative response reported by Mizell (Fleming and Tassava, 1981;Mizell, 1968). The developing mammalian limb bud possesses an endogenous ability to undergo a partial regenerative response in vitro and in vivo, indicating that regenerative ability is enhanced during development (Chan et al, 1991;Deuchar, 1976;Wanek et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Following the lead of Marcus Singer's studies on the neurotrophic influence in amphibian limb regeneration (Singer, 1952), Mizell reported on induced regeneration of amputated newborn opossum hind limbs by implantation of neural tissues (Mizell, 1968). However, in an effort to replicate these studies, Fleming and Tassava reported that anatomical variability in the timing of skeletal outgrowth of the opossum hindlimb, and not neural tissue grafts, could account for the partial regenerative response reported by Mizell (Fleming and Tassava, 1981;Mizell, 1968). The developing mammalian limb bud possesses an endogenous ability to undergo a partial regenerative response in vitro and in vivo, indicating that regenerative ability is enhanced during development (Chan et al, 1991;Deuchar, 1976;Wanek et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…When regenerative events are considered the product of cycles of evolutionary loss and gain, it can lead to potential solutions for regenerative failure restricted to specific animal groups and not universal across phylogenetic groups. For example, the approach of identifying key neurotrophic regulators of salamander limb regeneration has resulted in promoting limb regeneration in nonregenerative frog species (Mitogawa, Makanae, & Satoh, 2018; Singer, 1951) but not in mammalian species (Fleming & Tassava, 1981). This suggests that a universal solution to regenerative failure in animals in general, and humans in particular, may not exist and that the solution to regenerative failure.…”
Section: Introductionmentioning
confidence: 99%